Improving skilled workers' performance in construction projects in Nigeria - Alhaji Ali, Zannah (2016)
Skilled workers’ performance is one of the crucial aspects of labour productivity that requires proper attention for effective projects delivery in the construction industry. The level of skilled workers’ low performance has been seen to be a major factor which contributes toward inefficient construction projects productivity. Therefore, the objectives of this research are to identify the causes of low skilled workers’ performance in construction projects and to recommend ways to improve skilled workers’ performance in construction projects in the Nigeria. The objectives were achieved through a structured quantitative method of questionnaire distributed to 150 responents from project manager, project engineer, site engineer and site supervision that are active in the Nigerian construction and 111 of the response were collected which was 74% of the response rate. The data were collected and analysed using Statistical Package for Social Science (SPSS) version 22.0. Mean ranking and analysis of variance (ANOVA) were used as tools to analyse the data. The findings shows that; low wages of skilled, lack of sufficient skill acquisition centres and lack of incentive schemes for skilled workers were the most significant causes of low skilled workers’ performance in the Nigerian construction industry. Similarly, proper supervision, supply of quality plants and equipment and good wages for skilled workers were the most significant ways to improve skilled workers’ performance in the Nigerian construction industry. The homogenous analysis indicates that there are significant differences in perception of respondents on few variables whereas majority of respondents have similarities in most of the variables. The research findings confirmed that, stakeholders in the Nigerian construction industry should strategise on motivation, training and retraining, conducive working condition, supply of quality materials and equipment, and proper site management in order improve skilled workers’ performance in Nigerian construction industry.